2000
DOI: 10.1038/sj.gt.3301318
|View full text |Cite
|
Sign up to set email alerts
|

Sustained delivery and expression of DNA encapsulated in polymeric nanoparticles

Abstract: Sustained release polymeric gene delivery systems offer increased resistance to nuclease degradation, increased amounts of plasmid DNA (pDNA) uptake, and the possibility of control in dosing and sustained duration of pDNA administration. Furthermore, such a system lacks the inherent problems associated with viral vectors. Biodegradable and biocompatible poly(DL-lactide-co-glycolide) polymer was used to enacapsulate pDNA (alkaline phosphatase, AP, a reporter gene) in submicron size particles. Gene expression me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(217 citation statements)
references
References 35 publications
7
200
1
3
Order By: Relevance
“…Nebulization of pharmacological agents encapsulated in PLG has been described, particularly for airway delivery of antituberculous therapy, 23 but the effect of nebulization on PLG-encapsulated plasmid DNA has not yet been studied. While encapsulation of the DNA potentially offers a way to both protect DNA from degradation 15 and also control its release, 7 analysis of DNA extracted from our microspheres, as well as in previous studies, 6 revealed a relative increase in the amount of nicked DNA compared to supercoiled. Whether this translates into loss of transfection efficiency remains unclear.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Nebulization of pharmacological agents encapsulated in PLG has been described, particularly for airway delivery of antituberculous therapy, 23 but the effect of nebulization on PLG-encapsulated plasmid DNA has not yet been studied. While encapsulation of the DNA potentially offers a way to both protect DNA from degradation 15 and also control its release, 7 analysis of DNA extracted from our microspheres, as well as in previous studies, 6 revealed a relative increase in the amount of nicked DNA compared to supercoiled. Whether this translates into loss of transfection efficiency remains unclear.…”
Section: Discussionsupporting
confidence: 49%
“…To determine the amount and structural integrity of pDNA incorporated during preparation of the PLG microspheres, pDNA was extracted from the microspheres using a method previously described. 6 Briefly, the microspheres (10 mg) were dissolved in chloroform (1.5 ml) and the pDNA extracted by serial ( Â 5) additions of TE buffer (0.5 ml each time). pDNA content was analysed by spectrophotometry (Unicam UV1, ThermoSpectronic, Cambridge, UK) at 260 nm.…”
Section: Microsphere Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the divalent metal cation Ca 2 þ could form ionic complexes with the nucleic acid backbone and may stabilize DNA structures, so the CaCO 3 nanoparticle-DNA complexes can effectively cross cell membranes by ion channel-mediated endocytosis. 39 Because of the dissolution of calcium carbonate in the low acidic medium of endosomal compartments, the calcium carbonate nanoparticles are dissolved in the endosome and destabilize it through osmotic imbalance, and finally deliver the genetic material out into the cytosol. 40 The electrostatic interaction of Ca 2 þ with negatively charged DNA makes the DNA stable against nuclease attack, so that DNA can slowly enter the nucleus without any degradation.…”
Section: Discussionmentioning
confidence: 99%
“…38,69 The encapsulation of pDNA within microspheres or NPs has also been shown to preserve their in vivo functional integrity when the contact time with lysosomal enzymes is shortened. 37,70,71 Prior research that followed the kinetics of tissue and cellular localization of NPs loaded with either Rh-6G or Nile red also showed that the injected NPs reach the retina rapidly, homing in on the RPE cells where they were still observed 4 months after the injection; encapsulated Rh-6G dye diffused slowly from the NPs and uniformly stained the retinal layers. 72 RPE cells, as main constituents in CNV, are known to quickly respond and adapt to environmental stresses such as ischemia and metabolic changes by expressing a number of various genes, 73 and have a major role in CNV because of their essential function in neural retina homeostasis.…”
Section: Pdna-loaded Nanoparticles Inhibit Cnv C Zhang Et Almentioning
confidence: 99%